The Role of Russian Entrepreneurs in the Creation of Crimean Resorts in the Late 19th — Early 20th Centuries (with Reference to Simeiz and Gurzuf) - Borschik, Natalia D. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This study aims to trace the main stages of the construction of resort villages on the southern coast of Crimea between the late nineteenth and early twentieth centuries and their specifics and evaluate the contribution of Russian entrepreneurs to the development of resort business in Crimea. Based on the body of sources kept in the funds of the Russian State Historical Archive and the State Archive of the Republic of Crimea, it is established that the leading role in the formation and prosperity of the most popular Crimean resorts, Simeiz and Gurzuf, belongs to famous Russian entrepreneurs, i.e. representatives of the Maltsov dynasty and P. I. Gubonin, respectively. Thanks to their efforts and investments, once deserted and abandoned areas became villages with a developed infrastructure comfortable for living. Also, the involvement of a wide range of professionals in the construction of villages, such as architects, engineers, builders, managers, gardeners, etc. can be considered key to the successful functioning of resorts. The author singles out features of new places of rest: Simeiz developed because of individual development in accordance with the owners’ tastes, and Gurzuf became a model of hotel business of the time. The author concludes that with the help of a flexible pricing policy, hotels, guesthouses, and cottages became available to wealthy visitors not only of noble origin. In its turn, the public vacationing in Crimea enthusiastically got acquainted with local attractions, which became the basis for the formation of the tourism industry in the region. Crimea ceased to be an elitist place of rest for the royalty and persons close to them at the turn of the twentieth century and turned into the “Russian Riviera”, a popular resort in Russia, whose progressive development was interrupted by the events of October 1917 and the subsequent Civil War.